Safety and tumour-specific immunological responses of combined dendritic cell vaccination and anti-CD40 agonistic antibody treatment for patients with metastatic pancreatic cancer: protocol for a phase I, open-label, single-arm, dose-escalation study (REACtiVe-2 trial) - Joachim G J V Aerts; Sjoerd H van der Burg; Martijn P Lolkema; Sai Ping Lau; Freek R van ’t Land; Marjolein Y V Homs; Casper H J van Eijck (BMJ Open)
Introduction The prognosis of patients with advanced pancreatic ductal adenocarcinoma (PDAC) is dismal and conventional chemotherapy treatment delivers limited survival improvement. Immunotherapy may complement our current treatment strategies. We previously demonstrated that the combination of an allogeneic tumour-lysate dendritic cell (DC) vaccine with an anti-CD40 agonistic antibody resulted in robust antitumour responses with survival benefit in a murine PDAC model. In the Rotterdam PancrEAtic Cancer Vaccination-2 trial, we aim to translate our findings into patients. This study will determine the safety of DC/anti-CD40 agonistic antibody combination treatment, and treatment-induced tumour-specific immunological responses.Methods and analysis In this open-label, single-centre (Erasmus Univsersity Medical Center, Rotterdam, Netherlands), single-arm, phase I dose finding study, adult patients with metastatic pancreatic cancer with progressive disease after FOLFIRINOX chemotherapy will receive monocyte-derived DCs loaded with an allogeneic tumour lysate in conjunction with a CD40 agonistic antibody. This combination-immunotherapy regimen will be administered three times every 2 weeks, and booster treatments will be given after 3 and 6 months following the third injection. A minimum of 12 and a maximum of 18 patients will be included. The primary endpoint is safety and tolerability of the combination immunotherapy. To determine the maximum tolerated dose, DCs will be given at a fixed dosage and anti-CD40 agonist in a traditional 3+3 dose-escalation design. Secondary endpoints include radiographic response according to the RECIST (V.1.1) and iRECIST criteria, and the detection of antitumour specific immune responses.Ethics and dissemination The Central Committee on Research Involving Human Subjects (CCMO; NL76592.000.21) and the Medical Ethics Committee (METC; MEC-2021-0566) of the Erasmus M.C. University Medical Center Rotterdam approved the conduct of the trial. Written informed consent will be required for all participants. The results of the trial will be submitted for publication in a peer-reviewed scientific journal.Trial registration number NL9723.